KINERJA LINGKUNGAN, SOSIAL, TATA KELOLA, DAN NILAI PERUSAHAAN: STUDI KASUS PADA PT ASTRA AGRO LESTARI TBK PERIODE 2015-2023 - Jovan Christian Tambunan; Endang Kiswara (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) factors on the firm value of PT Astra Agro Lestari Tbk during the period 2015–2023. Firm value is measured using three key indicators: Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), while ESG performance is assessed through the GRI Index and ESG_DS. In addition to ESG, leverage (measured by Debt-to Equity Ratio/DER) and company size (measured by total assets) are also examined to evaluate their combined relationship with firm value.The research uses a qualitative descriptive analysis approach grounded in legitimacy theory, which emphasizes how companies align their operations with societal norms and expectations to gain acceptance. Data were collected from annual reports, sustainability reports, and secondary sources such as news articles and academic journals. The findings indicate that ESG performance is closely associated with fluctuations in profitability, with improvements in ESG scores often coinciding with higher ROA, ROE, and NPM, particularly in certain years. However, leverage and company size also significantly influence this dynamic.Overall, the study highlights the importance of integrating sustainability practices into business strategies to enhance long-term firm value. It also supports the legitimacy theory, suggesting that transparency and alignment with social expectations strengthen a company's position among stakeholders.